Evolution of tet(A) variant mediating tigecycline resistance in KPC-2-producing Klebsiella pneumoniae during tigecycline treatment. (March 2022) - Liao, Wenli; Wang, Lingbo; Zheng, Xiangkuo; Zhang, Ying; Chen, Tao; Zhou, Cui; Xu, Ye; Chen, Lijiang; Zhou, Tieli
Highlights: Direct in vivo evidence that tet (A) changes can lead to tigecycline treatment failure in Klebsiella pneumoniae infection. K. pneumoniae carrying both tet (A) mutation and bla KPC-2, leading to increased tigecycline resistance during treatment. First report describing tigecycline resistance of K. pneumoniae first increasing and subsequently decreasing in vivo. ABSTRACT: Objectives: This study investigated the underlying mechanism of the evolution of tigecycline resistance during treatment in a patient infected with Klebsiella pneumoniae harbouring bla KPC-2 . Methods: A total of seven clonal K. pneumoniae strains were continuously isolated from a patient during hospitalisation. Antimicrobial resistance in the strains was determined by antimicrobial susceptibility testing. Multilocus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE) were performed to explore the homology of the isolates. Whole-genome shotgun (WGS) analysis and cloning experiments were used to investigate the underlying mechanism of the evolution of tigecycline resistance. Results: All of the isolates had a minimum inhibitory concentration (MIC) for tigecycline of 4 µg/mL, except strain FK6768 that had a MIC of 32 µg/mL. Carbapenem-resistant K. pneumoniae strains (FK6614, FK6768 and FK6809) were consecutively isolated from faeces at different times. Antimicrobial susceptibility testing indicated that tigecycline resistance increased in FK6768 and subsequently decreased in FK6809, which attracted our attention. WGS and further bioinformatics analysis showed a homology for the three faecal isolates of >99%. The bla KPC-2 carbapenemase gene and a tet (A) mutation were found in tigecycline-resistant isolate FK6768. Subsequent cloning experiments confirmed the contribution of a tet (A) variant to reduced tigecycline susceptibility. Conclusion: Here we report a K. pneumoniae isolate carrying both tet (A) mutation and the bla KPC-2 gene, which led to increased tigecycline resistance during tigecycline treatment. This is the first report describing tigecycline resistance of K. pneumoniae first increasing and subsequently decreasing in vivo .